IMPLEMENTASI ALGORITMA FP-GROWTH UNTUK SISTEM REKOMENDASI BUKU DI PERPUSTAKAAN UKDW - Rama Novta Miraldi; Antonius Rachmat Christanto; Budi Susanto (Universitas Kristen Duta Wacana, 2015)
The number of collections in a library will be increase along with the growth of the library. The Library of Universitas Kristen Duta Wacana (UKDW) also has a large number-of books collection in order to provide literature and resources service to students. Wen the number of collection is very large, we need a retrieval system that will help anyone to find the needed resoLtrces. This system has a recommendation feature to provide related books or resources. This feature will help users to find similar literature/resources or related topic with what they need. This paper will describe about the main design and implementation of the book recommendation based on FP-Growth algorithm. Based on the experiments, this system can provide 60.78% of accuracy for related books recommendation.